Review Paper on Dynamic Mechanisms of Data Leakage Detection and Prevention - Shivakumara, T; Patil, Rajshekhar M; MS, Muneshwara (International Journal of Computer Sciences and Engineering, 2019)
Today’s world needs most of the things would be automated, the machine would be able to do itself everything by its own, from initiation of job to till the decision-making capabilities. Similarly the Security of the data needs the automated, selfdecision and self-protective proactive mechanisms. Since, the existing tools and mechanisms are semi-automated still it needs the human intervention to update and configure the security layers and features. This paper gives the summarized view of the existing work carried out so far in the area of data security – data leakage detection and prevention.